2023
DOI: 10.1021/jacs.2c11331
|View full text |Cite
|
Sign up to set email alerts
|

Highly Altered State of Proton Transport in Acid Pools in Charged Reverse Micelles

Abstract: Transport mechanisms of solvated protons of 1 M HCl acid pools, confined within reverse micelles (RMs) containing the negatively charged surfactant sodium bis(2-ethylhexyl) sulfosuccinate (NaAOT) or the positively charged cetyltrimethylammonium bromide (CTABr), are analyzed with reactive force field simulations to interpret dynamical signatures from TeraHertz absorption and dielectric relaxation spectroscopy. We find that the forward proton hopping events for NaAOT are further suppressed compared to a nonionic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 81 publications
0
1
0
Order By: Relevance
“…The X@RONa clusters seemed to be thermodynamically more favored than other types of sodium alkoxide aggregates. , Spontaneous generation of X@RONa was always observed as long as halide anions were present, suggesting that NaH would behave similarly, although the direct observation of cluster formation cored by solid NaH was prohibitively difficult. Single-crystal X-ray diffraction data revealed that such endohedral mixed aggregates resembled reverse micelles, , wherein 12 lipophilic alkyl side chains positioned themselves outwardly, while the ions were located inside the cage (Scheme c). Its all-around aliphatic exterior shell and interchangeable ionic interior could make a potential phase-transfer catalyst that can carry insoluble NaH into organic solvents.…”
mentioning
confidence: 99%
“…The X@RONa clusters seemed to be thermodynamically more favored than other types of sodium alkoxide aggregates. , Spontaneous generation of X@RONa was always observed as long as halide anions were present, suggesting that NaH would behave similarly, although the direct observation of cluster formation cored by solid NaH was prohibitively difficult. Single-crystal X-ray diffraction data revealed that such endohedral mixed aggregates resembled reverse micelles, , wherein 12 lipophilic alkyl side chains positioned themselves outwardly, while the ions were located inside the cage (Scheme c). Its all-around aliphatic exterior shell and interchangeable ionic interior could make a potential phase-transfer catalyst that can carry insoluble NaH into organic solvents.…”
mentioning
confidence: 99%